Sacred queer stories Ugandan LGBTQ+ refugee lives and the Bible - Van Klinken, A. S. 1982-; Stiebert, Johanna; Sebyala, Brian; Hudson, Fredrick; Muyunga-Mukasa, Tom Rogers; Nyanzi, Stella 1974- (Woodbridge James Currey, 2021)
An invaluable insight into the narrative politics and theologies of LGBTQ+ life-storytelling, a key text for those in African Humanities, Queer Studies, Religious Studies, and Refugee Studies.
Front Cover -- Table of Contents -- List of Illustrations -- Notes on Authors and Contributors -- Glossary and Abbreviations -- Acknowledgement -- Foreword -- Introduction -- PART I: Ugandan LGBTQ+ Refugee Life Stories -- STORY 1 - It's my nature, this is who I am -- STORY 2 - It's not like heaven here -- STORY 3 - Here we are free to express ourselves without fear -- STORY 4 - I consider this as my new family -- STORY 5 - Personally, I think God is gay -- STORY 6 - Angels don't have a gender -- STORY 7 - God loves me more than they love me -- STORY 8 - I just wanted an opportunity to express myself -- STORY 9 - I was chased away from the garden of heaven -- STORY 10 - First and foremost, I want to be a free person -- STORY 11 - God has a purpose for us all -- STORY 12 - God doesn't make mistakes -- PART II: Inter-reading Ugandan LGBTQ+Life Stories and Bible Stories -- 1 - Inter-reading Life Stories and Bible Stories -- 2 - Daniel in the Homophobic Lions' Den -- POEM - The Company of Men (Tom Rogers Muyunga-Mukasa) -- 3 - Jesus and the Guys Charged with Indecency -- POEM - Accused of a Sodomy Act (Tom Rogers Muyunga-Mukasa) -- 4 - Reflection: A Postcolonial and Self-reflexive Reading -- Conclusion -- Bibliography -- Index of Names and Subjects -- Index of Biblical References -- Previously published titles in the series.
Description based on publisher supplied metadata and other sources
Keywords: Bible; Electronic books; Kenya ; Nairobi; Uganda